Genetic insights into fetal growth and measures of glycaemic regulation and adiposity in adulthood: a family-based study - Mette Hollensted; Claus T. Ekstrøm; Oluf Pedersen; Hans Eiberg; Torben Hansen; Anette Prior Gjesing (BMC, 2018)
Abstract Background The genetics of fetal insulin release and/or action have been suggested to affect fetal growth, adult insulin resistance and adult body composition. The genetic correlation between body composition at birth versus glycaemic regulation and body composition in adulthood have, however, not been well studied. We therefore aimed to investigate these genetic correlations in a family-based cohort. Methods A Danish family cohort of 434 individuals underwent an oral glucose tolerance test with subsequent calculation of surrogate measures of serum insulin response and insulin sensitivity. Measures of fetal growth were retrieved from midwife journals. Heritability and genetic correlations were estimated using a variance component model. Results A high heritability of 0.80 was found for birth weight, whereas ponderal index had a heritability of 0.46. Adult insulin sensitivity measured as Matsuda index was genetically correlated with both birth weight and ponderal index (ρG = 0.36 (95% CI: 0.03; 0.69) and ρG = 0.52 (95% CI, 0.15; 0.89), respectively). Only birth weight showed a significant genetic correlation with adult weight (ρG = 0.38 (95% CI: 0.09; 0.67)) whereas only ponderal index was genetically inversely correlated with fasting insulin (ρG = - 0.47 (95% CI: - 0.86; - 0.08) and area under the curve for insulin release during the oral glucose tolerance test (ρG = - 0.66 (95% CI: - 1.13; - 0.19)). Individual as well as combined adjustment for 45 selected birth weight, obesity and type 2 diabetes susceptibility gene variants did not affect the correlations. Conclusions The genetics of both birth weight and ponderal index appear to be under the same genetic influence as adult insulin resistance. Furthermore, ponderal index and adult insulin release seem to be partly shared, as well as the genetics of birth weight and adult weight. Word count abstract: 281.